Jonathan Stökl, Prophecy in the Ancient Near East. A Philological and Sociological Comparison (Culture and History of the Ancient Neat East 56; Leiden – Boston: Brill, 2012) - Pikor, Wojciech (The Biblical Annals, 2015)
Book review : Jonathan Stökl, Prophecy in the Ancient Near East. A Philological and Sociological Comparison (Culture and History of the Ancient Neat East 56; Leiden – Boston: Brill, 2012). Pp. 297. € 110, 151. ISBN 978-9-004-22992-1.